Segmenting, Targeting, and Positioning Analysis of Platinum iB KPR Purchase Decisions with Murabahah Agreement - Wikantari, Maria Assumpta; Judijanto, Loso; Syamsuri, Helmy; Dhamayanti, Sylvia Kartika; Supriadi, Yudi Nur (IQTISHODUNA: Jurnal Ekonomi Islam, 2024)
The increasing competition demands competitive advantage that should be owned by each company and requires a proper marketing strategy. The number of competitors is increasingly making consumers have many alternative options to get a product that is in accordance with expectations. BTN syariah is consistent in its core business namely housing finance in accordance with the visit of Bank BTN itself which is the leading bank in financing with mortgage products or residential financing. This purpose of this study aims to analyze and examine the factors of segmenting, targeting and positioning aspect on consumer purchase decisions of iB Platinum KPR product with murabahah contracts at BTN Syariah Mataram Branch Office. The research used the quantitative with regression analysis method. The sampling method used purposive sampling and the number of samples used in this study amounted to 55 respondents source was distribution online questionnaires via WhatsApp to Customers of BTN Syariah who had purchased KPR Platinum iB with murabahah contract. The data were analysed used IBM SPSS version 22 and analysis was carried out by several tests such as validity test, realibility test, classic assumption test, linear regression analysis and coefficient of determination test. The results of this study indicate that the segmenting, targeting and positioning, has a significant effect on purchase decisions of iB Platinum KPR product with murabahah contracts at BTN Syariah Mataram Branch Office. The findings of this study can be reference uses as a reference for future researchers  who will study similar problems. This research can also be a reference for companies to always be able to maintain aspects of segmenting, targeting and positioning aspect in designing and determining effective and efficient markering policies.